2022
DOI: 10.3389/fpsyg.2022.917630
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive networks detect structural patterns and emotional complexity in suicide notes

Abstract: Communicating one's mindset means transmitting complex relationships between concepts and emotions. Using network science and word co-occurrences, we reconstruct conceptual associations as communicated in 139 genuine suicide notes, i.e., notes left by individuals who took their lives. We find that, despite their negative context, suicide notes are surprisingly positively valenced. Through emotional profiling, their ending statements are found to be markedly more emotional than their main body: The ending sente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Recent applications of cognitive networks to the study of suicide notes have provided unique insights into the structure of their emotional contents. For instance, Teixeira et al (2021) and Stella et al (2022) found, with different methodologies, that suicide notes consisted of an overwhelming majority of positively-valenced words that exhibited a compartmentalized structure, such that positively-versus negatively-valenced words were often connected with one another (Showers, 1992). Moreover, Stella et al (2022) found that suicide notes contained a higher degree of emotional complexity than notes written by a non-suicidal control group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent applications of cognitive networks to the study of suicide notes have provided unique insights into the structure of their emotional contents. For instance, Teixeira et al (2021) and Stella et al (2022) found, with different methodologies, that suicide notes consisted of an overwhelming majority of positively-valenced words that exhibited a compartmentalized structure, such that positively-versus negatively-valenced words were often connected with one another (Showers, 1992). Moreover, Stella et al (2022) found that suicide notes contained a higher degree of emotional complexity than notes written by a non-suicidal control group.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Teixeira et al (2021) and Stella et al (2022) found, with different methodologies, that suicide notes consisted of an overwhelming majority of positively-valenced words that exhibited a compartmentalized structure, such that positively-versus negatively-valenced words were often connected with one another (Showers, 1992). Moreover, Stella et al (2022) found that suicide notes contained a higher degree of emotional complexity than notes written by a non-suicidal control group. Together, these findings reflect that suicide notes may contain a unique emotional and lexical footprint.…”
Section: Introductionmentioning
confidence: 99%
“…Stella et al (2022) concluded that the notes describe highly structured and contrasting narratives of emotions, more complex than expected by null models and for populations without clinical issues. Based on network science, psycholinguistics, and the semantic framework theory, Teixeira et al (2021) attempted to develop a representational network of suicidal ideation expressed in the same pool of suicide notes analyzed by Stella et al (2022). Findings suggested that the connections between terms with positive and negative valence give rise to a significantly greater degree of balance than in a null model (a model constructed under the assumption that the network under study has no particular patterns or special structure, where the affective structure is random), and in a linguistic baseline model capturing mental wanderings in the absence of suicidal ideation.…”
mentioning
confidence: 99%
“…In fact, the material found in suicide notes can be quite complex and informative. Stella et al (2022), used procedures related to network science and analyzed genuine suicide notes written by 143 by individuals who successfully committed suicide. This pool of information was developed by Schoene and Dethlefs (2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation